2019
DOI: 10.4314/bajopas.v11i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic assessment of renal length in apparently healthy students of college of health sciences, Bayero University, Kano

Abstract: In persons with normal renal function, renal length has been found to be the most important marker for assessing renal function. Ultrasound is readily available, non invasive and provides a direct and easy method of determining renal length. The aim of this study is to determine the range of normal renal measurements among the students of College of Health Sciences, BUK. Renal lengths of apparently healthy volunteered students were measured using Mindray DP 3.5MHz curvilinear transducer. Maximum bipolar length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The proximate analysis revealed that eliminating mineral matter from coal demineralization has a high potential as indicated by other studies (Manoj and Elcey, 2010;Manoj et al, 2009;Okoro, Asadu, and Maxwell, 2018;Usman et al, 2019) and is appropriate coal for solid fuel combustion. The proximate and ultimate analyses of the undemineralization and demineralization coal samples are presented in Table 1.…”
Section: Results Of Proximate and Ultimate Analysesmentioning
confidence: 64%
See 2 more Smart Citations
“…The proximate analysis revealed that eliminating mineral matter from coal demineralization has a high potential as indicated by other studies (Manoj and Elcey, 2010;Manoj et al, 2009;Okoro, Asadu, and Maxwell, 2018;Usman et al, 2019) and is appropriate coal for solid fuel combustion. The proximate and ultimate analyses of the undemineralization and demineralization coal samples are presented in Table 1.…”
Section: Results Of Proximate and Ultimate Analysesmentioning
confidence: 64%
“…Low sulphur content as depict by the demineralize coal signifies that the solid fuel can be used to generate power with reduced emissions to the environment (Behera et al, 2017). Calorific value required for generating electricity falls within the range 2700 -9500 Kcal/Kg (Usman et al, 2019). The Maiganga undemineralize coal has the calorific value of 5179.80 kcal/kg while demineralized coal calorific value is higher 5210.38 kcal/kg, this result depict that the demineralization of the coal is beneficial since the higher is the calorific value signifies the better the quality of the coal (Behera et al, 2017) and a major term for heat generation capacity (Usman and Maitera, 2015).…”
Section: Results Of Proximate and Ultimate Analysesmentioning
confidence: 99%
See 1 more Smart Citation